ANALISIS HASIL BELAJAR MAHASISWA DALAM MATA KULIAH KOMPUTER AKUNTANSI - Suharyono Suharyono; Teguh Widodo (Politeknik Negeri Bengkalis, 2017)
Abstract: Based on SKKNI that one of the competency units that must be mastered by students, the students are able to operate computer accounting applications. This study was conducted to determine whether there are differences in learning results in computer accounting subjects between classes A, B and C. The Test used is Mann-Whiteney nonparametric test. The number of population in this research is 81 students of 3rd semester of D3 Program of Business Administration. The results of this study indicate that the learning achievements or the ability of students in the subject of computer accounting using MYOB between class A, class B and class C is no different. Differences of lecturers who teach computer accounting subjects in each class have no effect toward student learning achievements. Key Words: comparison, score, computer, accounting, students.